Investigating the behavioural intentions of museum visitors towards VR : A systematic literature review - Li, Yi Fei; Mohd Kamal, Othman (Elsevier Ltd., 2024)
This study investigates the behavioural intentions of museum visitors towards Virtual Reality (VR) technology, spanning the years 2010–2023. It evaluates literature quality, explores research theories, and identifies trends. Findings indicate that most museum visitors hold positive attitudes towards VR, necessitating further research on generational perspectives. Quantitative research methods dominate (77.8%), with 38.9% employing the Technology Acceptance Model (TAM) or its extensions. Key influencing factors include perceived usefulness, information quality, perceived ease of use, and psychological cognition. The study underscores the importance of comprehending generational differences among museum visitors and advocates for adopting comprehensive theoretical models in future research within the museum domain. This research contributes to understanding how museum visitors engage with VR technology, emphasising nuanced approaches considering generational variations and recommending more inclusive theoretical frameworks.